Logic – Grammar – Logic - Forsberg, Anders Niklas (Walter de Gruyter GmbH & Co. KG, 2024)
A commonly shared view when it comes to Wittgenstein’s philosophy was that one of the main focuses of the early Wittgenstein’s work was the concept of logic and that the turn away from logic towards the concept of grammar and “grammatical investigations” of “ordinary language” is the defining characteristic of “later Wittgenstein.” There are many different ways of spelling out differences and similarities here. What has gone more or less unnoticed, though, is that when Wittgenstein writes the remarks collected as On Certainty, there are very few mentions of “grammar,” and the few mentions there are show that this concept now does very little philosophical work. Interestingly, though, the concept of logic is much more frequently employed, and it is also a concept Wittgenstein on which is really working. This paper asks why the concept of logic again seems to have taken on a larger role in Wittgenstein’s latest period.
Logika - gramatika - logika
Keywords: Grammar; Logic; Wittgenstein; On Certainty; grammatical investigations; ordinary language; Gramatika; logika; Wittgenstein; o jistotě; gramatická zkoumání; běžný jazyk